A General Approach for Buckled Bulk Composites by Combined Biaxial Stretch and Layer‐by‐Layer Deposition and Their Electrical and Electromagnetic Applications. (6th March 2019) - Liu, Zhongsheng; Wan, Fayu; Mou, Linlin; Jung de Andrade, Monica; Qian, Dong; Wang, Run; Yin, Shougen; Li, Kun; Chen, Hong; An, Baigang; Hu, Zhizhi; Wang, Hongzhi; et al.
Abstract: Fabrication of high quality stretchable conductors that show bulk structure, high electrical conductivity, and stable conductance under large deformations is crucial for wearable electronics and soft robots. A key difficulty here is to introduce buckled structure into the conductive phase of the bulk conductors and overcome the lateral crack problem in the conductive phase during buckle formation. In this paper, a general approach is introduced for fabricating novel buckled bulk composite (BBC) stretchable conductors based on common conductive nanomaterial by using sequential biaxial stretch–release and layer‐by‐layer deposition to provide alternating buckled conductive layers and elastomer layers. This biaxial stretch is used to keep the width of elastomers unchanged before and after stretching, to avoid the lateral crack formation of the conductive layer. This method can be applied to common nanoparticles, such as silver nanoparticles, silver nanowires, single‐walled carbon nanotubes, and graphenes. The BBCs exhibit high conductance, uniform structure, and stable conductance during deformation and temperature change, which are demonstrated as applications in electrical interconnects, electrothermally driven artificial muscles, electromagnetic interference shielding materials, and reconfigurable antennas. Abstract : A general approach for fabricating novel buckled bulk composites based on common conductive nanomaterial by using sequential biaxial stretch–release and layer‐by‐layer deposition to provide alternating buckled conductive layers and elastomer layers is demonstrated. The composites exhibit high conductance, uniform structure, and stable conductance during deformation and temperature change, which encourage their applications in electronics and electromagnetics.